If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + 2t = 232 Solving 6b + 2t = 232 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2t' to each side of the equation. 6b + 2t + -2t = 232 + -2t Combine like terms: 2t + -2t = 0 6b + 0 = 232 + -2t 6b = 232 + -2t Divide each side by '6'. b = 38.66666667 + -0.3333333333t Simplifying b = 38.66666667 + -0.3333333333t
| 4(2+1)=2(3-x) | | 26=-16x^2+4x+16 | | 5p+7=3(4-q) | | 4n-5=3 | | x*x-18x+81=4+81 | | -14=-(-2+2) | | -x*x+x+.25=1.25 | | 2m+6=2(2m+3)-2 | | -x*-x+x+.25=1.25 | | 3(c-8)+13=5c+5 | | -4.4=2x+25.6 | | 4.2z=-4(0.6-1.2) | | 2mx^2-mx+1=0 | | 3(6-x)-8=2 | | 5x+6x-64=3x-65 | | 4v-2=10 | | 5x^2=2x+1 | | 6x+19x=25 | | 4x+2+6x-1=13x+1 | | 18-6y=0 | | 4x+3=42 | | 10=3f+1 | | 2b+1=7 | | 4x-5=-1x-30 | | -2x-10+7x=6x+14-4x | | x+14=-32-9 | | -6y+13=-5(y-4) | | 13x=-7-3-20 | | 4x+3x=-35 | | Y+13-7y=-5(y-4) | | 16x+2=-17 | | 22-5x+9x=-2(-6x+5) |